2008
DOI: 10.4103/0970-0358.44921
|View full text |Cite
|
Sign up to set email alerts
|

The association between blood groups and maxillofacial deformities

Abstract: Background:Blood group is a genetic characteristic which is associated with some diseases and deformities. Multifactorial characteristics of facial development make it difficult to predict a genetic pattern in a specific maxillofacial deformity, but epidemiological evaluations can reveal relationships between such deformities and some genetic characteristics or accompanied diseases, and this will help to recognise and treat them. The aim of this study is evaluation of the relationship between blood groups and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…shows that maxillofacial deformities were greater with blood Group B and were least with blood Group A, suggestive of ABO blood groups as one of the etiologic factors for these deformities. [ 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…shows that maxillofacial deformities were greater with blood Group B and were least with blood Group A, suggestive of ABO blood groups as one of the etiologic factors for these deformities. [ 36 ]…”
Section: Discussionmentioning
confidence: 99%
“…15 Other report showed that oral pathologies like dermatophytosis are common in blood group A. 16 Study by Vivek et al 17 showed blood group O had a greater chances for periodontitis while Gheisari et al 18 showed blood group B have a greater likelihood of association with maxillofacial deformities and least with blood group A.…”
Section: Discussionmentioning
confidence: 98%
“…The most commonly impacted teeth in the mouth are the third molars. In previous studies in Saudi Arabia, the prevalence of at least one impacted third molar ranged from 12.31% to 40.5% [ 15 , 16 ]. In our study, 34.6% of the 856 included cases, or about one-third of the population, has one impacted third molar or more.…”
Section: Discussionmentioning
confidence: 99%